Carotenoids Extraction from Orange Peels Using a Thymol-Based Hydrophobic Eutectic Solvent - Konstantinos Terlidis; Vassilis Athanasiadis; Theodoros Chatzimitakos; Eleni Bozinou; Stavros I. Lalas (AppliedChem, 2023)
The food industry produces substantial amounts of waste, which can cause a lot of environmental issues. However, such waste is also a valuable source of bioactive substances that can potentially be used either by the food industry or other types of industries, in the production of medicines, nutraceuticals, cosmetics, etc. The present study proposes a novel approach to extract such bioactive compounds from orange peel waste using hydrophobic eutectic solvents synthesized with thymol and fatty acids (hexanoic and octanoic acid). A response surface methodology was employed to optimize the extraction conditions and achieve maximum recovery of carotenoids. The optimal hydrophobic eutectic solvent consisted of thymol and hexanoic acid at a molar ratio of 2:1, and the optimum extraction was achieved using a solvent-to-solid ratio of 12:1 and a temperature of 20 °C for 78 min; this resulted in a recovery of 259.45 μg of total carotenoids per g of dry matter, which is a significantly higher recovery compared to common organic solvents. Based on the above, it is demonstrated that hydrophobic eutectic solvents is a promising solvent that can be used to extract bioactive compounds from orange peel waste.